Improved cyclic softening behavior of ultrafine-grained Cu with high microstructural stability. (June 2019) - Xue, P.; Wang, B.B.; An, X.H.; Ni, D.R.; Xiao, B.L.; Ma, Z.Y.
Abstract: We report that the uniform and stable microstructure essentially ameliorate the cyclic softening of the ultrafine-grained (UFG) Cu prepared by friction stir processing (FSP) and then enhance its low-cycle fatigue properties. In lieu of the fatigue-induced grain coarsening, dislocation and grain boundary (GB) activities play crucial roles in accommodating the cyclic plasticity. In addition, the protrusion and small cracks near the GB regions rather than shear bands are main surface damage morphologies that lead to its final fatigue failure. Graphical abstract: Unlabelled Image